The Development of Biology Learning Tools with Project Based Learning (PjBL) Model to Improve The Sustainable Reserve Food Garden(SRFG) program of grade X students in SMAN 1 Singosari - Imam Fikry Fanani; Mimien Henie Irawati; Susilowati Susilowati (Indonesian Journal of Biology Education, 2018)
SRFG (Sustainable Reserve Food Garden) is a program has an important role to achieve self sufficiency food in community. This research and development has aims to development of learning tools with Project Based Learning (PjBL) model to improve SRFG program for grade X students . Test development product consists of validity test, practicality test and effectiveness test. Procedure of development adapts model of development Thiagarajan (1974) which only consists of 3 steps: 1) define; 2) design; and 3) develop. The results  of  validation test showed that learning tools is very valid because the average percentage of assessment over 85%. The result of  practicality test showed that learning tools is very practical  because it can be applied in the class and the average percentage of  practical level is 95.3%. The results of  effectiveness test showed that learning tools is very effective because of increase in test scores, the average percentage of student activity is  91.2%, the products has positive respond by 81.1% of students and teacher.